1983
DOI: 10.1083/jcb.97.2.317
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba discriminates internally between digestible and indigestible particles.

Abstract: The capacity of Acanthamoeba to distinguish nutritive yeast particles from nonnutritive plastic beads during phagocytosis was investigated. When cells were allowed to phagocytose yeast to capacity, endocytosis stopped and subsequent presentation of particles (either yeast or beads) did not result in further uptake. By contrast, when cells were allowed to phagocytose plastic beads to capacity and a second dose of particles was presented (either yeast or beads), the cells exocytosed the internal particles and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 21 publications
(23 reference statements)
2
27
1
Order By: Relevance
“…Subsequent to particle uptake, Acanthamoeba have the ability to distinguish vacuoles containing digestible and indigestible particles. For example, Bowers and Olszewski (1983) have shown that the fate of vacuoles within Acanthamoeba is dependent on the nature of particles, latex beads versus food particles. Vacuoles containing food particles are retained and digested, while latex beads are exocytosed, upon presentation of new particles.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to particle uptake, Acanthamoeba have the ability to distinguish vacuoles containing digestible and indigestible particles. For example, Bowers and Olszewski (1983) have shown that the fate of vacuoles within Acanthamoeba is dependent on the nature of particles, latex beads versus food particles. Vacuoles containing food particles are retained and digested, while latex beads are exocytosed, upon presentation of new particles.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to particle uptake into a vacuole, Acanthamoeba exhibit the ability to distinguish vacuoles containing digestible and indigestible particles. For example, Bowers & Olszewski (1983) have shown that the fate of vacuoles within Acanthamoeba is dependent on the nature of particles, latex beads vs. food particles. Vacuoles containing food particles are retained and digested, whereas latex beads are exocytosed, upon presentation of new particles.…”
Section: Feedingmentioning
confidence: 99%
“…Some studies suggest, however, that the fate of a phagosome and the particle contained therein can be regulated by the degradability of the particle (79–83) and its hydrophilicity (83,84). A ’state‐of‐digestion‐sensing system’ is also suspected to exist in Acanthamoeba (85) and Dictyostelium (86). If the chemical nature of phagosome cargo is relevant to phagosome development, then it is not surprising that, in some systems, the maturation kinetics of LBP seems slower than that of phagosomes containing degradable contents [e.g.…”
Section: Entering Latex Infectionsmentioning
confidence: 99%